2017
DOI: 10.1089/jayao.2016.0023
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Loss to Follow-Up Care Among Childhood Cancer Survivors

Abstract: Purpose: Surveillance for long-term complications related to previous cancer therapy can help diagnose/ manage chronic health conditions in childhood cancer survivors and improve survivor quality of life. However, a challenge to delivering long-term care to childhood cancer survivors is loss to follow-up; many patients discontinue care at specialized survivor care centers. The purpose of this study was to examine patterns of loss to follow-up among a cohort of childhood cancer survivors. Methods: This retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 24 publications
2
64
0
1
Order By: Relevance
“…3 Another Cochrane review of interventions for improving communication with children and adolescents regarding cancer found weak evidence supporting few interventions such as art therapy and computer-assisted learning. [87][88][89] Interventions may include enhancing clinician communication training with evidence-based recommendations (Table 3) and the perspectives of children and adolescents. [87][88][89] Interventions may include enhancing clinician communication training with evidence-based recommendations (Table 3) and the perspectives of children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…3 Another Cochrane review of interventions for improving communication with children and adolescents regarding cancer found weak evidence supporting few interventions such as art therapy and computer-assisted learning. [87][88][89] Interventions may include enhancing clinician communication training with evidence-based recommendations (Table 3) and the perspectives of children and adolescents. [87][88][89] Interventions may include enhancing clinician communication training with evidence-based recommendations (Table 3) and the perspectives of children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Survivors who attend cancer survivor clinics are educated about their risk for specific late effects, receive recommended surveillance for detection of treatment‐related health conditions, and are referred to specialists if late effects are identified. However, some survivors may be followed in cancer survivor clinics as young children/adolescents but may not have access to survivor care as they age into adulthood . Other survivors often receive their healthcare from providers who may be less familiar with survivor care .…”
Section: Introductionmentioning
confidence: 99%
“…Rokitka et al . investigated the visiting habits of 370 CCS who had been treated at their own facility, and reported that the ratio of follow‐up care declined over time, from 91.2% in post‐treatment years 1–5, to 68.5% in post‐treatment years 6–10, and then to 47.7% in post‐treatment years 11–15 …”
Section: Discussionmentioning
confidence: 99%